Steffen Auring, Søren Baggesen, Finn Hauberg Mortensen, Søren Petersen, Marie-Louise Svane, Erik Svendsen, Poul Aaby Sørensen, Jørgen Vogelius og Martin Zerlang: Dansk Litteraturhistorie 5. Borgerlig enhedskultur 1807-48. (Gyldendal, 1984). 591s., ill. - Skovmand, Roar (Historie/Jyske Samlinger, 1987)
-